Hydrogen production with integrated CO2 capture via sorbent enhanced reforming - Lesemann, Markus; Mays, Jeff; Clough, Peter T.; Oakey, John; Adedipe, Tosin; Duncan, Angus (SSRN, 2022)
GTI Energy has been developing a novel process technology for hydrogen production from natural gas with inherent carbon capture. The GTI process, based on sorbent enhanced reforming (SER), has the advantage that it captures CO2 inherently in the process via a pre-combustion technique instead of secondary capture from a flue gas stream. This approach is fundamentally different from conventional technologies such as steam methane reforming (SMR) and autothermal reforming (ATR) which require additional process steps to avoid CO2 emissions. The inherent carbon capture capability results in step-out economics of the GTI process. The GTI process is based on GTI’s Hydrogen Generator (CHG) technology which converts natural gas and steam into H2 and CO2 in separate streams. The inherent carbon capture in the GTI process leads to its higher carbon capture potential, its substantially lower capital cost (by 40-60%) and substantially smaller footprint compared to the conventional approaches, resulting in overall lower levelized cost of hydrogen (by 10-30%). In its optimized configuration, carbon capture rates over 97.5%, with 10% lower levelized cost of hydrogen (LCOH) and ~50% reduction in CAPEX compared to conventional SMR with CO2 capture are achievable. By relaxing the carbon capture rate to 96%, a LCOH ~20% lower than the SMR case can be achieved. LCOH and CAPEX advantages of the process compared to Autothermal Reforming (ATR) are even more pronounced. Development of the process technology is currently supported by the U.S. Department of Energy (DOE) and by the U.K. Department for Business, Energy, and Industrial Strategy (BEIS). DOE has been supporting the development and operation of a 0.071 MWth pilot plant at GTI’s main test facility near Chicago, USA, to demonstrate the process chemistry and fluidized bed operation. Under BEIS funding, a team comprised of Cranfield University, GTI Energy, and Doosan Babcock has been developing a 1 MWth pilot plant at a dedicated new test site at Cranfield University in the UK (“HyPER Project”).
Keywords: hydrogen; CO2 capture; pre-combustion capture; sorbent; sorbent enhanced reforming